2012
DOI: 10.1089/cmb.2011.0301
|View full text |Cite
|
Sign up to set email alerts
|

The 5′-3′ Distance of RNA Secondary Structures

Abstract: Recently Yoffe et al. observed that the average distances between 5 ′ -3 ′ ends of RNA molecules are very small and largely independent of sequence length. This observation is based on numerical computations as well as theoretical arguments maximizing certain entropy functionals. In this paper we compute the exact distribution of 5 ′ -3 ′ distances of RNA secondary structures for any finite n. We furthermore compute the limit distribution and show that already for n = 30 the exact distribution and the limit di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…We propose that range 2 is the correct one for the comparison and that the persistence length of the exterior loop should be much higher than 2.1 nm to get results consistent with the width of the histograms (Supplementary Figure S2c–e). Under these assumptions, all the measured RNA molecules give an ℒ between 9 and 16 nt, which is consistent with theoretical predictions ( 14 17 ). It is known that magnesium ions are important for the structural stability of RNA molecules ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We propose that range 2 is the correct one for the comparison and that the persistence length of the exterior loop should be much higher than 2.1 nm to get results consistent with the width of the histograms (Supplementary Figure S2c–e). Under these assumptions, all the measured RNA molecules give an ℒ between 9 and 16 nt, which is consistent with theoretical predictions ( 14 17 ). It is known that magnesium ions are important for the structural stability of RNA molecules ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Han et al. ( 17 ) found a probability distribution for the 5′-3′ end distance from which the end-to-end separation of random RNA sequences ‘were distinctively lower than those reported by Yoffe et al. ’.…”
Section: Introductionmentioning
confidence: 90%
“…That the polymer-zeta property does not hold for RNA has also been observed in the context of the limit distribution of the 5'-3' distances of RNA secondary structures [42]. Here it is observed that long arcs, to be precise arcs of lengths O(n) always exist.…”
Section: Resultsmentioning
confidence: 56%
“…These recursions have been derived in several different contexts, e.g. force induced RNA denaturations [ 6 ], the investigate of loop entropy dependence [ 9 ], the analysis of FRET signals in the presence of single-stranded binding proteins [ 5 ], as well as in mathematical studies of RNA panhandle-like structures [ 3 , 4 ].…”
Section: Theorymentioning
confidence: 99%
“…Panhandles have been reported in particular for many RNA virus genomes. Several studies [ 1 - 4 ] agree based on different models that the two ends of single-stranded RNA molecules are typically not far apart. On a more technical level, the problem to compute the partition function over RNA secondary structures with given end-to-end distance d , usually measured as the number of external bases (plus possibly the number of structural domains) arises for instance when predicting nucleic acid secondary structure in the presence of single-stranded binding proteins [ 5 ] or in models of RNA subjected to pulling forces (e.g.…”
Section: Introductionmentioning
confidence: 99%